Tailoring and functionalizing the graphitic-like GaN and GaP nanostructures as selective sensors for NO, NO2, and NH3 adsorbing: a DFT study - Mollaamin, Fatemeh; Monajjemi, Majid (Springer Science and Business Media LLC, 2023)
Langmuir adsorption of gas molecules of NO, NO2, and NH3 on the graphitic GaN and GaP sheets has been accomplished using density functional theory. The changes of charge density have shown a more important charge transfer for GaN compared to GaP which acts both as the electron donor while gas molecules act as the stronger electron acceptors through adsorption on the graphitic-like GaN surface. The adsorption of NO and NO2 molecules introduced spin polarization in the PL-GaN sheet, indicating that it can be employed as a magnetic gas sensor for NO and NO2 sensing.The partial electron density states based on "PDOS" graphs have explained that the NO and NO2 states in both of GaN and GaP nanosheets, respectively, have more of the conduction band between - 5 and - 10 eV, while expanded contribution of phosphorus states is close to gallium states, but nitrogen and oxygen states have minor contributions. GaN and GaP nanosheets represent having enough capability for adsorbing gases of NO, NO2, and NH3 through charge transfer from nitrogen atom and oxygen atom to the gallium element owing to intra-atomic and interatomic interactions. Ga sites in GaN and GaP nanosheets have higher interaction energy from Van der Waals' forces with gas molecules.